Strategi Pemasaran Digital Terhadap Keputusan Pembelian Generasi Z Urban Dengan Perilaku Generasi Z Sebagai Moderasi - Masadi, Mahnun; Nurhadi, Ahmad (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
Changes in consumer behavior in the digital era create a big challenge for business actors in aligning marketing strategies with the preferences of the digital native generation. This study aims to analyze the influence of digital marketing strategies on purchasing decisions and test the role of Generation Z's behavior as moderation variable. Phenomena such as FOMO, paylater features, and online reviews are the main background. This research aims to provide in-depth insight into the strategies faced by business in the digital era and provide recommendations for optimizing digital channels according to business needs. The research method used is a survey with an explanatory research approach to examine the causal relationship between variables. Data was collected through a questionnaire from 100 Generation Z active online shoppers in the last three months, then analyzed using a quantitative method with the SEM-PLS Technique with the help of SmartPLS software to test the measurement model (outer model) and structural model (inner model). The results showed that Digital Marketing Strategy had a positive and significant effect on Purchase Decisions with a path coefficient (ß) of 0.452 and a significance value of p < 0.05. Generation Z Behavior was shown to significantly moderate and strengthen the influence of digital marketing strategies on purchase decisions with an interaction value of 0.218 (p = 0.003). This structural model has strong predictive accuracy with an R-Square value of 0.684, which means that independent and moderate variables are able to explain 68.4% of the variation in purchasing decisions. This study recommends business optimize interactive visual content and utilize social proof to effectively reach the unique characteristics of Generation Z.